1997
DOI: 10.1590/s0104-11691997000100003
|View full text |Cite
|
Sign up to set email alerts
|

Adolescer e adoecer: perfil de saúde-doença de adolescentes de uma unidade básica de saúde do município de São Paulo

Abstract: (AYRES, 1994).Contraditoriamente, embora as práticas assistenciais de saúde voltada para os adolescentes se orientem predominantemente para agravos de origem biológica, o perfil de mortalidade desse grupo populacional evidencia uma causa marcadamente extra-biológica, com predominância de causas externas (LOLIO et al. 1990;YUNES & PRIMO, 1985) o que poderia em parte explicar a inadequação dessas práticas em transformá-lo. AYRES (1990)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
2
0
1
Order By: Relevance
“…A gravidez na adolescência é um grave problema no Brasil, que se acentuou na última década, com profundas repercussões para a jovem mãe e seu filho (5) . (20) . geradores falados por meio das palavras geradoras" (8) .…”
Section: Resultsunclassified
“…A gravidez na adolescência é um grave problema no Brasil, que se acentuou na última década, com profundas repercussões para a jovem mãe e seu filho (5) . (20) . geradores falados por meio das palavras geradoras" (8) .…”
Section: Resultsunclassified
“…TMD has been associated with several painful and non-painful conditions in adults. 14,15,23 Additionally, it has been demonstrated that the presence of comorbidity tends to increase the severity and the disability related to the involved conditions, as well as make worse their prognostic. 7 Because there is a lack of information regarding the associations between TMD and other conditions among adolescents, our study is justified.…”
Section: Discussionmentioning
confidence: 99%
“…This information was collected and evaluated in a list, which was presented to legal guardians, containing the most frequent diseases reported among Brazilian youth. 24 These diseases were grouped as follows: 1) Respiratory diseases (bronchitis, rhinitis, asthma, sinusitis, pulmonary emphysema, and pneumonia); 2) Gastrointestinal diseases (gastro-esophageal reflux; irritable bowel syndrome, constipation, gastritis/ulcer, and colitis); 3) Endocrine diseases (diabetes, hypothyroidism, hyperthyroidism, and hypoglycemia); 4) Diseases which may include painful conditions (fibromyalgia, rheumatoid arthritis, erythematous lupus, and migraines); 5) Cardiac/Hematologic Diseases (anemia, hypertension, cholesterol, and heart problems); 6) Psychological conditions (depression, anorexia/bulimia, and attention deficit hyperactivity disorder); and 7) Gynecological diseases (polycystic ovary and endometriosis).…”
Section: Methodsmentioning
confidence: 99%